Implementation of curriculum development in islamic religious education at al islam mranggen elementary madrasah, sukoharjo regency, central java - Alfian Eko Rochmawan; Nur Hidayah; Latifah Khoirul Hasanah; Ngatmin Abbas; Muh. Hasbi Khilal Zuhri (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study examines the implementation of curriculum development in Islamic religious education at Al Islam Mranggen Elementary Madrasah in Sukoharjo Regency, Central Java. Utilizing a qualitative approach, data collection methods include interviews, observations, and document analysis. The findings reveal that the madrasah adheres to curriculum guidelines from the Ministry of Religious Affairs, integrating Islamic teachings into various subjects. Despite efforts to cultivate a religious atmosphere, challenges such as limited resources and parental involvement hinder effective implementation. In conclusion, the study sheds light on curriculum development in Islamic education, emphasizing the need to align curriculum goals with broader educational objectives.